Relationship between endogenous colony stimulating factors and apoptosis in human colon cancer cells: role of cyclo-oxygenase inhibitors - Calatayud, Sara (2001)
1. Nonsteroidal anti-inflammatory drug (NSAID) usage is associated with gastrointestinal inflammatory damage and aggravation of gut inflammatory conditions. NSAIDs also exert a preventive effect against colon cancer that seems to be due to increased colon cell apoptosis. NSAIDs have been shown to modulate the release of colony stimulating factors (CSFs) in some cells. In the present study we analysed the effect of these drugs on secretion of CSFs and apoptosis in human colon epithelial cells (HT-29). 2. HT-29 cells secreted bioactive levels of GM-CSF, G-CSF and M-CSF when stimulated with IL-1ß and TNF-α, and diclofenac (10(−7) – 10(−4) M), indomethacin (10(−7) – 10(−4) M) and sodium salicylate (10(−5) – 10(−2) M) induced concentration-dependent increases in GM-CSF secretion. 3. Reduced secretion of G-CSF and M-CSF and increased cell apoptosis were observed with the highest concentrations of these non-selective NSAIDs. 4. No changes in any CSF release or HT-29 cell apoptosis were detected in the presence of the COX-2 selective inhibitor DFP (10(−7) – 10(−4) M). 5. Neither the exogenous addition of CSFs nor the blockade of secreted CSFs modified apoptosis in HT-29 cells stimulated with cytokines and/or NSAIDs. 6. These results suggest that colon epithelial cells can contribute to local inflammatory responses by releasing CSFs and thus extend the life span of local leukocytes. Modulation of CSF levels by non-selective NSAIDs may be involved in the pro-inflammatory effects of these agents in the gut.